Akad Perbankan Syariah dan Penerapannya dalam Akta Notaris Menurut Undang-Undang Jabatan Notaris - Pandam Nurwulan (Fakultas Hukum Universitas Islam Indonesia, 2018)
This study examines, first, why the binding guarantee in Shariah banking deed still practice the concept used by conventional banking. Second, how the notary formulates Sharia banking deeds in accordance with Law on Notary, and third, the ideal requirements for a notary in formalizing Sharia banking deeds. The research method used is normative legal research by processing and analyzing data in a qualitativedescriptive approach. The results show that, first, the binding guarantee of Sharia banking deeds still uses the concept of conventional banking guarantee because there are no Sharia rules/regulations governing a matter of binding guarantee for Sharia deeds (there is a legal vacuum/recht vacuum). As a result, the practice of guarantee binding procedures for Sharia banking deeds uses mortgage and fiduciary rights as is commonly practiced by conventional banking. Secondly, in formulating Sharia deeds, a notary should follow the Law on Notary without leaving the Sharia principles and mechanism/procedure for making a Notary deed. Third, the notary inaugurating Sharia deeds must be well acquainted with Sharia principles, which are based on the divinity principle in Sharia deeds, making it ideal if the notary who legalizes the Sharia deeds is a Muslim.